Repeatability of the Calibration Protocol for Emg Evaluation of the Occlusion With the Teethan Device - Bogdanov V. (Acta Medica Bulgarica, 2024)
The aim of the study was to investigate the repeatability of the calibration protocol performed by the Teethan® device (Teethan S.p.A. Italy) for surface electromyography (sEMG) when biting on cotton rolls to eliminate the effect of occlusal contacts.